Estimation of Forage Productivity and Business Feasibility Analysis at the Integrated Agricultural Center of PT Arutmin Indonesia Site Asamasam - Seftia Norazizah; Fajri Maulana; Endang Wawan; Nurul Yakin; Muhammad Syahwal Ade Putra (Asian Journal of Social and Humanities, 2024)
The purpose of this study is to support the development of cattle fattening business in the Integrated Agricultural Center (SPT) managed by PT Arutmin Indonesia. The research method used in this study is Field Work Practice (PKL) which is carried out at PT Arutmin Indonesia Site Asamasam, Simpang Empat Sungai Baru Village, Jorong District, Tanah Laut Regency, South Kalimantan Province. This street vendor lasts for three months, from March 4, 2024 to June 3, 2024. The results of this study show that the productivity of indigofera, sorghum, elephant grass and odot grass in SPT is 2.92 tons, 4.5 tons, 2.9 tons, and 0.278 tons respectively with a dry matter content of 4.08% respectively; 4,8%; 6,57%; and 7.48%. Based on the results of the feasibility analysis of the cattle fattening business in the tax return. The cattle fattening farm business in the SPT is feasible to run because it has a turnover of Rp. 400,000,000 with PP for 5 years and the company will break even if the BEP price is Rp. 15,321,525 and successfully sells 15 cows.